Deep mentoring guiding others on their leadership journey - Reese, Randy D.; Loane, Robert, 1969- (Downers Grove, IL : IVP Books, 2012)
This book is designed to help you know better how to come alongside others as a guide and a friend, to invest in their spiritual formation and leadership. If you want long-term impact on the lives of future leaders, how you guide must be as important as the content you impart. Only then will you see lifelong change and empowerment in those you mentor. --from publisher description
Noticing God's already-present action -- Paying attention -- Storied way: what we learn from editing our lives -- Learning from those who have come before us -- Foundation: a beginning -- Preparation: finding our way -- Contribution: leading out of who we are -- Multiplication: finishing well -- Guiding the formation of others -- Imitating Jesus? Way with others -- Christian leadership formation: the nature of our work -- Lessons from those who have come before us -- Big picture: getting a lifelong perspective -- Macro-observations from Clinton's leadership emergence study -- Practices for the long haul.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christian leadership; Mentoring -- Religious aspects -- Christianity; Discipling (Christianity); Spiritual direction; RELIGION / Christian Ministry / Pastoral Resources; Electronic books